Improving Marketing Performance Based on Analysis of Comparative and Competitive Advantages: An Empirical Study on Java Coffee Agroindustry in Jember-Indonesia - Kurniawan, Bagus Putu Yudhia; Halil, Halil; Abdul Razzaq, Abdul Rasid bin bin; Jumintono, Jumintono (ExcelingTech, 2020)
This study aims to determine the priorities of the Java Coffee Jember-Indonesia agroindustry marketing performance improvement strategy based on the analysis of comparative and competitive advantage. The study was conducted using the census method or complete enumeration, which was conducted on all Java Coffee Jember-Indonesia agroindustry which numbered 15 companies. The analysis technique used to analyze research data is the Policy Analysis Matrix (PAM), the TOWS matrix for formulating alternative strategies, and determining priorities using the Analytical Hierarchy Process (AHP). The results showed that the Java Coffee Jember-Indonesia agroindustry has a comparative and competitive advantage. This is indicated by the coefficient of Domestic Resource Cost (DRC = 0.69) and Private Cost Ratio (PCR = 0.4) which is smaller than 1.00. Java Coffee Jember-Indonesia's agroindustry position is in cell V with the choice of strategy is to hold and maintain, and can be managed through market penetration strategies and product development. The priority strategies implemented to improve the marketing performance of Java Coffee Jember-Indonesia agroindustry are to penetrate the market, improve product quality through the implementation of Standard Operating Procedures (SOP) in accordance with SNI-01-3542-1994, collaborate with major raw material providers, recruit human resources who have special abilities and market development, increase the ability of human resources through training, and diversify products and packaging.